Systematic Review: Prevalensi dan Dampak Infeksi Malaria pada Wanita Hamil dan Neonatal - Yuni Purwatiningsih; Sinta Dewi Lestyoningrum; Sunaryo Sunaryo; Dewi Puspita (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Globally, malaria cases in the world reached 241 million cases in 2020 and increase from the previous year. Malaria infection in pregnant women was reported in 33 countries, and the cases were estimated at 11.6 million (34%). Malaria infection can increase maternal and fetal morbidity and mortality, including anemia in pregnancy, low birth weight, premature birth, stillbirth, and small gestation age, and congenital malaria. This article discusses pregnant women's malaria infection prevalence and maternal and neonatal outcomes. This paper is a systematic review by searching for articles using electronic databases from Pubmed and ScienceDirect using keywords “Malaria” and “Pregnancy” or “Pregnant Women” and “Outcome” or “Impact” and “Maternal” or “Neonatal”. The selection of articles used the PRISMA guidelines which were then analyzed in a narrative manner. Based on the article search results obtained 10 articles that meet the criteria for analysis. The prevalence of malaria infection in pregnancy is still high. Reported outcomes in pregnancy, birth, and neonates include preterm birth, low birth weight, small gestation age, maternal anemia, and maternal and neonatal mortality. The role of health workers is very important to prevent malaria infection in pregnancy so that it does not result in adverse health impacts for maternal and neonatal.